Prevalence of Macrovascular Complications and Their Associated Risk Factors Among Type 2 Diabetic Patients Attending In A Tertiary Level Hospital (KYAMC Journal, 2017)
Background: Macrovascular complications cause much of the serious morbidity and mortality in patients with diabetes. The aim of the study was to determine the prevalence and risk factors of different macrovascular complications among type 2 diabetic patients.Materials and Methods: We studied two fifty cases of type 2 diabetic patients in this cross-sectional study which was conducted in the out-patient department of BIRDEM hospital, Bangladesh. The randomly selected patients were evaluated for the presence of coronary heart diseases (CHD), stroke and peripheral vascular diseases (PVD) through the review of their registered diabetic guide book. We included sociodemographic information, blood pressure, anthropometry (height, weight, body mass index) and lipid profile of the patients. Glycaemic status was assessed by HbA1c (HbA1c was categorized into 3 groups) and plasma glucose levels. We used logistic regression analysis to determine and quantify the association of CHD, stroke and PVD with various risk factors. Results: Two hundred and fifty cases of type 2 diabetic patients (male 129 and female 121 were studied. The prevalence of macro-vascular complications was 28.8%. Among them CHD was 21.2% (95% CI: 16.13- 26.27%), stroke in 8.4% (95% CI: 4.96-11.84%) and PVD in 7.2% (95% CI: 4-10.4%). Logistic regression models showed that macrovascular complications were more common in females; the risk increased significantly with age, longer duration of diabetes, lacking of physical exercise, presence of hypertension, HbA1c, Fasting Blood Glucose (FBG) and blood glucose 2 hours ABF.Conclusions: CHD is the most common macrovascular complication among type 2 DM patients. Advanced age, longer duration of diabetes, hypertension, poor glycaemic control, lacking of physical exercise etc. are significant risk factors of macrovascular complications in type 2 diabetic patients.KYAMC Journal Vol. 7, No.-1, Jul 2016, Page 662-667